2009
DOI: 10.3923/itj.2009.403.410
|View full text |Cite
|
Sign up to set email alerts
|

Hardware/Software Co-Design Implementations of Elliptic Curve Cryptosystems

Abstract: This paper presents a survey of hardware/software co-design implementations of elliptic curve cryptosystems. A critical study of the underlying finite field, the representation basis, and the partitioning schemes of these implementations is conducted. The study shows that all implementations are implemented over binary fields GF(2 m ) and the implementations that use polynomial basis are more than implementations that use normal basis for finite field arithmetic. The study also shows that the best partitioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Implementation of ECC Arithmetic over Finite Fields are described in [14] on cadence 45nm technology for SKA, BKA and OKA with area, power and timing analysis. [15] has shown ASIC implementations of ECC by designing the finite field arithmetic on hardware and remaining operations of the ECC on software. [16] demonstrated that "hardware-based accelerators have acceptable performance-cost ratio with appropriate efficiency-flexibility trade-off".…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of ECC Arithmetic over Finite Fields are described in [14] on cadence 45nm technology for SKA, BKA and OKA with area, power and timing analysis. [15] has shown ASIC implementations of ECC by designing the finite field arithmetic on hardware and remaining operations of the ECC on software. [16] demonstrated that "hardware-based accelerators have acceptable performance-cost ratio with appropriate efficiency-flexibility trade-off".…”
Section: Introductionmentioning
confidence: 99%